Birth Order, Father's Occupation and Family Size are Strongly Associated with Thinness Among Bengalee Adolescent Girls of Darjeeling District, West Bengal (India) - Debnath, Mampi; Tigga, Pushpa Lata; Mondal, Nitish; Sen, Jaydip (Journal of Nepal Paediatric Society, 2016)
Introduction: Undernutrition is a major issue in the developing countries such as India. The country has the largest adolescent population in the world and one of the primary focuses of nutritional assessment among them is undernutrition. The present cross-sectional study tries to determine the prevalence of thinness among adolescent girls of Darjeeling district using thinness (BMI-for-age) and to ascertain the effects of different socio-economic and demographic variables on the same.Material and methods: The study was carried out among 387 school-going adolescent girls aged 9-14 years belonging to the Bengalee Hindu caste populations (BHCP). The prevalence of thinness was assessed using recently proposed international BMI-for-age cut-offs of Cole et al.Results: The prevalence of overall thinness was 23.77%. The distribution of mild (Grade I), moderate (Grade II), and severe (Grade III) thinness were 17.31%, 4.39% and 2.07%, respectively. The results of the binary logistic regression analysis showed that birth order, family size and father’s occupation were significantly associated with overall prevalence of thinness (p